Molecular orientation of individual LCP particles in injection-moulded PPS/LCP blends - Kestenbach,H.-J. (2003)
Polarized light microscopy was used to investigate the presence of preferred molecular orientation in the LCP phase of PPS/LCP blends after injection moulding. Normal birefringence effects appeared to be complicated by artifacts due to sample preparation and by the complex nature of polarized light transmission through a multicomponent sample. It was found, however, that, during low-temperature cutting of optically transparent thin sections on a standard microtome, individual LCP particles could be separated from the PPS matrix, and their birefringence analyzed separately. Preferred orientation was detected only in LCP fibrils which dominated in skin regions, but not in droplet-shaped particles which had formed in core regions. Quantitative measurements indicated that the molecular orientation of the fibrils increased linearly with their length-to-diameter aspect ratios which ranged from 15 to 50. Even for the highest aspect ratios, however, the degree of orientation was always less than that which could easily be introduced into pure LCP thin-film samples by manual shearing.